Climate-Related Financial Risk In Indonesia: A Systematic Literature Review And Policy Implications - Tarada Berlian Megananda; Dara Sagita Triski (International Journal of Management and Business Economics, 2026)
Climate change has shifted from an environmental concern into a material financial risk capable of disrupting financial-system stability through both physical and transition-risk channels. Indonesia, as an archipelagic nation with high hydrometeorological disaster vulnerability and an economy still dependent on carbon-based commodities, faces dual exposure to both risk channels. This study aims to map the extent to which financial risk and climate change have been examined in Indonesian academic literature, and to assess whether Indonesia's current condition is a matter of concern or remains within a safe zone. A systematic literature review of national and international journal publications from 2017-2026 was conducted, supplemented by secondary-data analysis of per-capita carbon dioxide emissions and official disaster data. The results show that research on this nexus has grown rapidly since 2022 yet remains behind international institutional studies in volume and methodological depth. Data indicate that Indonesia's per-capita CO2 emissions remain below the world and Asian averages, but the upward trend is steep, compounded by a high frequency of hydrometeorological disasters and structural dependence on fossil energy. The study concludes that Indonesia occupies an 'elevated-but-manageable risk zone' - not yet a systemic crisis, but no longer within a safe zone - requiring accelerated integration of climate-risk management into macroprudential policy, stronger data infrastructure, and a just acceleration of the energy transition.